Efektivitas Penggunaan Video Pembelajaran berbasis GeoGebra terhadap Kemampuan Taruna/i dalam Memahami Aplikasi Matematika Maritim - Luthfiana Tarida (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2021)
Universities, lecturers and students/ cadets must be able to adapt and innovate to changes in the learning paradigm due to the impact of Covid-19. Online lectures currently require supporting media so that the essence of knowledge construction can still be achieved. Learning videos are thought to have effectiveness on knowledge construction. This research aims to analyze the effectiveness of using GeoGebra-based instructional videos on the ability of cadets to understand maritime mathematics applications. The learning video contains standard mathematics material of IMO Model Course 7.03. Mathematical materials are related to the maritime field and visualized using GeoGebra software. This type of research is a quantitative study with a Pre-Experimental Design design, and a One Group Pretest-Postest Design model. The research sample consisted of 33 cadets of the 2020 batch of Nautics AMN. The data was collected by means of tests (pre-test post-test), interviews and literature studies. The pre-test and post-test data were not normally distributed so they were processed using the Wilcoxon test assisted by SPSS software. The results showed that the use of GeoGebra-based learning videos was significantly more effective in the ability of cadets to understand maritime mathematics applications. Video lessons can increase the motivation of cadets at AMN to learn mathematics. This is because the application material for maritime mathematics, which is partly in the form of geometry, is greatly helped by the 3D animation visualization from GeoGebra.